The Use of Neurotropin in the Treatment of Ischemic Strokes - Sikorska, M. V.; Vizir, I. V.; Belenichev, I. F.; Laponov, O. V.; Popazova, O. O.; Сікорська, Марина Володимирівна; Візір, Ірина Володимирівна; Бєленічев, Ігор Федорович; Лапонов, Олександр Віталійович; Попазова, Олена Олександрівна (USA : Medwin Publishers, 2021)
This research analyzed the results of treatment of 32 patients with ischemic stroke with the drug neurotropin, an antioxidant with antihypoxant properties, evaluated its clinical efficacy, the effect on the processes of protein oxidative modification, and the antioxidant activity of the blood. The control group consisted of 15 people, in whose traditional therapy neurotropin was not included. The study showed that the use of neurotropin in complex therapy contributed to the regression of neurological deficit, caused a positive effect on the oxidative metabolism of the brain, hemostasis, and had a hypolipidemic effect. Thus, the inclusion of neurotrophin in the complex therapy of ischemic strokes is reasonable and expedient.
Keywords: ischemic stroke; oxidizing metabolism of brain treatment